Toxic responses of different organs following occupational exposure to sub-threshold limit value levels of paving asphalt fumes. Issue 2 (7th February 2017) - Neghab, Masoud; Derisi, Forough Zare; Hassanzadeh, Jafar; Dirin, Vahid; Heidari, Sasan
ABSTRACT: The main purpose of this study was to ascertain whether occupational exposure to asphalt fumes, under normal working conditions, is associated with any hepatotoxic, nephrotoxic, or hematotoxic response. This was a cross-sectional study in which 210 subjects (80 exposed and 130 reference subjects) were investigated. Using standard methods, atmospheric concentrations of total particulate and benzene-soluble fractions of asphalt fumes were measured. Additionally, urine and blood samples were taken from subjects for complete blood count, white blood cell differential test, urinalysis, and routine biochemical tests of kidney and liver function. Both groups were similar as far as their demographic variables and smoking habits were concerned. The levels of exposure to total particulate and benzene-soluble fractions were estimated to be 0.9 ± 0.2 and 0.32 ± 0.09 mg m −3, respectively (mean ± SD), both of which being lower than the existing threshold limit values. Statistically, significant associations between exposure to asphalt fumes and changes in most liver and kidney function tests and complete blood count parameters provided circumstantial evidence in favor of the notion that exposure to sub-threshold limit value levels of total particulate and benzene-soluble fractions is associated with early liver and kidney dysfunction as well as hematological disorders.